Exact Sequences of BCK-Modules - ÜLKER, ALPER (Fuat Usta, 2022)
BCK-modules were introduced as an action of a BCK-algebra over an Abelian group. Homomorphisms of BCK-modules form an exact sequence which is called BCK-sequence. In this paper, we study homomorphisms of BCK-modules. We show that this homomorphisms have a module structure. Moreover, we show that sequences of Hom functors are BCK-sequences.
Keywords: BCK-algebra; BCK-module; Exact Sequence; Hom Functor